Differentiation of Regions According to the Standard of Living of the Population - R. V. Fattakhov; M. M. Nizamutdinov; V. V. Oreshnikov (Мир новой экономики)
The relevance of this work is determined by the important problems of improving living standards in Russia, increasing the welfare of the population, and reducing poverty. High differentiation of the country’s regions also creates additional risks associated with forming undesirable migration flows of both population and business. Studies show that while being a leader in one area, a region may lag in other areas. It is necessary to determine how interrelated the various indicators of living standards in the subjects of the Russian Federation are. The research methods are based on the analysis of indicators of living standards of the population of Russian regions. In particular, the authors analyzed current and retrospective values, compared the values of indicators in different regions of the country, correlation and cluster analysis. The study formed integral indicators of regional development in five areas that characterize the population’s living standard to carry out calculations. The analysis results showed that there is no significant linear correlation between 22 selected private indicators of living standards in the vast majority of cases. The prospects of the study lie in further identification of ways to improve the situation, considering the specifics of the ratio of various indicators of living standards.